The Evaluation of Bioelectrical Activity of Pelvic Floor Muscles Depending on Probe Location: A Pilot Study. (11th December 2013) - Halski, Tomasz; Ptaszkowski, Kuba; Słupska, Lucyna; Dymarek, Robert
Abstract : Objectives . The main objective was to determine how the depth of probe placement affects functional and resting bioelectrical activity of the PFM and whether the recorded signal might be dependent on the direction in which the probe is rotated. Participants . The study comprised of healthy, nulliparous women between the ages of 21 and 25. Outcome Measures . Bioelectric activity of the PFM was recorded from four locations of the vagina by surface EMG and vaginal probe. Results . There were no statistically significant differences between the results during functional sEMG activity. During resting sEMG activity, the highest bioelectrical activity of the PFM was observed in the L1 and the lowest in the L4 and a statistically significant difference between the highest and the lowest results of resting sEMG activity was observed (P = 0.0043 ). Conclusion . Different electrodes placement during functional contraction of PFM does not affect the obtained results in sEMG evaluation. In order to diagnose the highest resting activity of PFM the recording plates should be placed toward the anterior vaginal wall and distally from the introitus. However, all of the PFM have similar bioelectrical activity and it seems that these muscles could be treated as a single muscle.